Biodistribution of intravenously delivered PEGylated carbon nanotubes to the rat brain cortex - Bruch, Gisele Eva; Dal Bosco, Lidiane; Cordeiro, Arthur P.; Cordeiro, Marcos F.; Sahoo, Sangram K.; Peixoto, Carolina; Klosterhoff, Marta C.; Romano, Luis Alberto; Fantini, Cristiano; Santos, Adelina P.; Barros, Daniela M. (Frontiers in Carbon, 2025)
Polyethylene glycol-functionalized single-walled carbon nanotubes (SWCNT-PEG) have been studied for many biomedical applications because of their unique physicochemical properties. Due to their reduced size and high stability in physiological media, SWCNT-PEG are candidates to cross the blood-brain barrier (BBB), potentially being used to treat central nervous system diseases that are currently unresponsive to pharmacological interventions because of the tightly regulated permeability of the BBB. In this study, we investigated the biodistribution of intravenously delivered SWCNT-PEG using Raman spectroscopy, as well as possible toxicological outcomes using morphological, histological, biochemical, and behavioral analyses. SWCNT-PEG were identified in the brain cortex, blood, spleen, and liver of rats. Biochemical and histological analyses did not reveal toxic effects in rats 24 h after SWCNT-PEG injection. Also, no behavioral impairments were observed in treated animals subjected to the Morris water maze task. Our preliminary experimental results clearly indicate that SWCNT-PEG were able to cross biological membranes and reach the rat brain cortex parenchyma (but not other brain structures) after systemic administration, without the presence of acute toxic effects. The biodistribution of SWCNT-PEG in a specific region of the brain tissue encourages further studies regarding the application of SWCNT in the neuroscience field.